(untitled) (Conferencea, 2023)
In the article, the health and physical development of students is strengthened and developed; Development and improvement of physical qualities; Forming the skills to maintain the body correctly during periods of inactivity and movement; Implementation of labor and homeland defense training; The issues of accustoming to physical training and sports and arousing their permanent interest in it have been reflected.